PWE-081 Comparison of elective and emergency cholecystectomies – a longitudinal cohort study with focus on inpatient stay. (22nd June 2015) - Spence, J; Sinha, Y; Zafar, Z; Iqbal, F; Cheruvu, C; Rao, V
Abstract : Introduction: Emergency cholecystectomy during index admission has become a standard of care in all major acute surgical units. However, with competing interests for emergency theatre time, the duration of inpatient stay has become a frustrating experience both for the surgical team and the patient. Method: A prospective longitudinal cohort study including all consecutive patients who underwent emergency and elective cholecystectomies over a six month period in a busy tertiary centre was undertaken. Demographic data, inflammatory markers, number of inpatient days and post op complications were analysed. In addition, number of previous admissions among patients waiting for elective cholecystectomies was analysed. Statistical tests including one way ANOVA and unpaired T test were used when appropriate. Results: 145 patients (Age: 50; range:16–85, M:F = 44:101) were admitted on an emergency basis and 161 patients (Age 51; range: 17–84, M:F= 36:125) were admitted to undergo elective cholecystectomies as day case procedure over a six month period. Based on intra-op findings, three subgroups of patients among emergency admissions were identified: biliary colic with thin walled gall bladder (n = 51; 13 with pancreatitis), acute cholecystitis with inflamed thick walled gall bladder (n = 78; 22 with pancreatitis) and complicated cholecystitis with empyema and perforation (n = 16). There was a significant difference in mean CRP and WCC levels (biliary colic: 21.9 and 9.4, acute cholecystitis: 85.1 and 11.7, complicated cholecystitis: 181.4 and 13.9, p = 0.000 and p = 0.002; one way ANOVA). There was a significant difference between the number of days between admission to operation for emergency (n = 145) and elective cases (n = 161) (4.1 vs 0, p = 0.000), and number of inpatient days for emergency (n = 145) and elective cases (n = 161) (6.6 vs 1.0, p = 0.000; unpaired T test). If the patients who had biliary colic and acute cholecystitis (excluding patients who had pancreatitis) were treated on an outpatient basis, a potential saving of 594 inpatient days could be done. Among patients who underwent elective cholecystectomies, 35 patients had A&E/acute admissions during the waiting period (149 days; range: 11–983). Majority of this subgroup of patients (n-27) waited for more than 50 days, implying that a second encounter with emergency services can be avoided if these patients get their elective surgery within this time period. Conclusion: Majority of emergency patients presenting with acute gall bladder symptoms can be managed on an outpatient basis with definitive surgery planned on a day case basis. This will save a significant number of inpatient days with obvious implications at a time of increasing bed pressures in the NHS. Disclosure of interest: None Declared.